Relocation of Earthquakes Hypocenter Using the Double Difference Method in Bali and Its Surrounding Areas - Irma Putri, Devi; Sukarasa, I Ketut; Darsono, Rudy; Tjahyo Baskoro, Winardi; Wendri, Ni Nyoman; Satriya Wibawa, I Made (BULETIN FISIKA, 2024)
A study on the relocation of earthquake hypocenters using the Double Difference method has been conducted in Bali and its surrounding areas. This research was carried out at the Center for Meteorology, Climatology, and Geophysics Region III Denpasar. The purpose of this study is to find out the distribution of earthquake hypocenters before and after the relocation and to know the continuity of earthquake hypocenters in the Bali region. The data used are arrival time data of 1,815 earthquake events from January 1, 2014 to December 31, 2023, and data from 26 earthquake recording stations.   The relocation method applied is the Double Difference method, which is processed with ph2dt and HypoDD. The relocation that has been carried out shows a good hypocenter position which is characterized by a residual value of travel time that is close to 0. The distribution of the earthquake hypocenter in the Bali area before the relocation spread throughout the region and after the relocation, the position of the hypocenter was getting closer to the source of the earthquake, namely in the subduction zone under the Bali area as shown in the cross-section results. In addition, based on the results of the analysis of the hypocenter of the earthquake after relocation, it was found that the trend of the hypocenter continued toward the subduction subduction zone.